Social And Economic Attachment In The Development Of The Creative Knitting Industry In Tanjung Enim - Lestari, Arum Lingga; Purnama, Dadang Hikmah; Yunindyawati, Yunindyawati (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to analyze the socio-economic embeddedness in the development of the knitting creative industry in Tanjung Enim, which is supported by the CSR program of PT Bukit Asam. The research employed a qualitative descriptive method with a case study approach. Data were collected through observation, interviews, and documentation involving knitting artisans and CSR representatives, then analyzed through data condensation, data display, and conclusion drawing and verification. The results show that the knitting creative industry has developed as a form of creative economy based on social collaboration, yet it remains dependent on external support from CSR Bukit Asam in terms of mentoring, training, and marketing. Based on Granovetter’s embeddedness theory, the relationship among artisans reflects relational embeddedness through trust, norms, and solidarity, while structural embeddedness is evident in the role of CSR as the main facilitator. The development efforts of the knitting industry are directed toward enhancing human resource capacity, product innovation, and expanding social networks and markets to achieve independence and sustainability as a competitive creative economy.